Arab navigation in the Indian Ocean before European dominance in South and Southeast Asia : a historical study - Islam, Arshad (Hamdard Foundation Pakistan, 2010)
Until qomparativelrye centt imes( mid l9th century)winds shaped navigation over seas. From simple boats,rafts and canoes they developed ships with masts which made it possible for human beings to roam around the various parts of the known world. Naturally the coastal people indulging in seafaring played a significant role in bringing nations closer to different races and creeds. With this association among various peoples through overseas trade began between different parts of the globe, particularly in the littoral lands of the Indian Ocean. The lands along the Oceania(littoral of the Indian Ocean)Arabia,India, Malaya and Indonesia enjoyed unique importance since the dawn of civilization. From the very beginning Arabs and Persians were linked through the lucrative maritime trade with the people of East Africa,the Western Indian coast,even upto Southeast Asia upto the coast of China. The coastarl egiono f the IndianO ceanw as a area of social and cultural diversity enriched with four different civilizations: the Perso-Arabic,the Indian,the Malayan/ Indonesian and the Chinese.The seaborne trade,enhanced by the land routes, generatead strong sense of unity between the peoples of different geographical regions.